ROCK MASS CLASSIFICATION IN BAWURAN AREA, YOGYAKARTA SPECIAL PROVINCE, INDONESIA - , SOMKHIT DALASANG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The traditional mining the main problem to risk for excavation, it is located in the southeast part of Yogyakarta special province, Indonesia. This mining will be built in the area that contains various types of rock, i.e. andesitic breccia, and tuffaceous sandstone. Before this underground structure will be constructed, the main problems that may occur during the excavation need to be considered which relating to rock mass instabilities. Thus, to minimize and avoid those problems, it is necessary to do the detail site investigation related to geological conditions in order to estimate the rock mass quality in this area. This research is mainly aimed to evaluate the rock mass classification by applying one empirical methods such as Rock Mass Rating (RMR) .The purpose of RMR system is to classify the quality of rock mass by using surface data, in order to guide the excavation method and also to give the recommendation of mining supports as well as the unsupported span and stand-up time. Moreover, according to RMR method, which depended on the rock mass conditions in the study area, this research has also tried to figure out the engineering potential risks that may occur during the mining construction and attempted to suggest the appropriate method to control and prevent such those potential risks. Based on RMR determination by using surface data, the qualities of rock masses in the study area are classified to be good and fair rock, the good rocks are found on andesitic and andesitic breccias (RMR=70-77, unsupported span is 8.3 m, stand-up time is 333.33 days)